Chapter 8 Phrenological Controversy and the Medical Imagination: 'A Modern Pythagorean' in Blackwood's Edinburgh Magazine - E. Shuttleton, David (Clio Medica: Perspectives in Medical Humanities, 2014)
Scottish Medicine and Literary Culture, 1726-1832 examines the ramifications of Scottish medicine for literary culture within Scotland, throughout Britain, and across the transatlantic world. The contributors take an informed historicist approach in examining the cultural, geographical, political, and other circumstances enabling the dissemination of distinctively Scottish medico-literary discourses. In tracing the international influence of Scottish medical ideas upon literary practice they ask critical questions concerning medical ethics, the limits of sympathy and the role of belles lettres in professional self-fashioning, and the development of medico-literary genres such as the medical short story, physician autobiography and medical biography. Some consider the role of medical ideas and culture in the careers, creative practice and reception of such canonical writers as Mark Akenside, Robert Burns, Robert Fergusson, Sir Walter Scott and William Wordsworth. By providing an important range of current scholarship, these essays represent an expansion and greater penetration of critical vision.